Mutant Single Nucleotide Polymorphism rs189037 in Ataxia-Telangiectasia Mutated Gene Is Significantly Associated With Ventricular Wall Thickness and Human Lifespan - Fu, Shihui; Hu, Jianqiu; Chen, Xiaoping; Li, Bo; Shun, Hongjuan; Deng, Juelin; Zhang, Yujie; Yao, Yao; Zhao, Yali (Frontiers in Cardiovascular Medicine, 2021)
In the current study, we aimed to determine the association of single nucleotide polymorphism rs189037 in ataxia-telangiectasia mutated (ATM) gene with cardiac structure and human longevity. Based on the China Hainan Centenarian Cohort Study performed in 18 cities and counties of Hainan Province, China, the current study enrolled 547 centenarians, 250 young participants aged 20–45 years, and 250 middle-aged and elderly participants aged 46–90 years. The frequency of TT genotype was significantly higher and that of CC genotype was significantly lower in middle-aged and elderly participants than in young (P = 0.012) and centenarian (P = 0.041) participants. There were no significant differences in the genotype and allele frequencies of SNP rs189037 between young and centenarian participants. Compared with CT genotype, TT genotype was positively and significantly associated with interventricular septum thickness (IVST) and left ventricular posterior wall thickness (LVPWT) in centenarian (IVST: P = 0.049; LVPWT: P = 0.047) and middle-aged and elderly (IVST: P = 0.008; LVPWT: P = 0.004) participants. Compared with CC genotype, TT genotype was positively and significantly associated with LVPWT in centenarian (P = 0.030) and middle-aged and elderly (P = 0.013) participants. Compared with CC genotype, CT genotype was negatively and significantly associated with left ventricular end diastolic diameter (LVEDD) in centenarian (P = 0.011) and middle-aged and elderly (P = 0.040) participants. The current study demonstrated that mutant rs189037 in the ATM gene was more commonly identified in middle-aged and elderly participants than in young and centenarian participants, was significantly associated with increased left ventricular wall thickness and volume, and could induce left ventricular eccentric hypertrophy and shorten human lifespan. Therefore, rs189037 without mutation might be an indicator of youth health and successful aging, whereas mutant rs189037 might hinder human longevity.